2019
DOI: 10.1007/s12576-019-00724-2
|View full text |Cite
|
Sign up to set email alerts
|

The local repolarization heterogeneity in the murine pulmonary veins myocardium contributes to the spatial distribution of the adrenergically induced ectopic foci

Abstract: An atrial tachyarrhythmias is predominantly triggered by a proarrhythmic activity originate from the pulmonary veins (PV) myocardial sleeves; sympathetic or adrenergic stimulation facilitates PV proarrhythmia. In the present study the electrophysiological inhomogeneity, spatiotemporal characteristics of the adrenergically induced ectopic firing and sympathetic nerves distribution have been investigated in a murine PV myocardium to clarify mechanisms of adrenergic PV ectopy. Electrically paced murine PV demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Notably, our previous study demonstrated that application of α 1 ‐adrenomimetics was unable to induce RMP depolarization in murine PV myocardium 53 . In addition, in another study, I K1 current remained unchanged under α 1 ‐stimulation in isolated canine caval veins cardiomyocytes 26 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Notably, our previous study demonstrated that application of α 1 ‐adrenomimetics was unable to induce RMP depolarization in murine PV myocardium 53 . In addition, in another study, I K1 current remained unchanged under α 1 ‐stimulation in isolated canine caval veins cardiomyocytes 26 .…”
Section: Discussionmentioning
confidence: 91%
“…Notably, our previous study demonstrated that application of α 1 -adrenomimetics was unable to induce RMP depolarization in murine PV myocardium. 53 In addition, in another study, I K1 current remained unchanged under α 1 -stimulation in isolated canine caval veins cardiomyocytes. 26 The species-specific channel-forming Kir2.x composition might underlie insensibility of this current to α1-adrenomimetics in mice and dogs 35 and sensitivity of I K1 in rats.…”
Section: The Role Of Protein Kinase C In Attenuation Of I K1 By α1-mentioning
confidence: 89%
“…In quiescent mouse PV [ 30 , 35 ], NE also induced automatic activity that appeared in the different forms (continuous or bursts of AP) already observed in spontaneously active preparations under basal conditions ( Section 5.1 ). NE was without effect on the LA.…”
Section: Pulmonary Veins: a Source Of Spontaneous Triggered And Catecholaminergic Automatic Activitymentioning
confidence: 98%
“…The latter is consistent with human observation: nerve filaments and ganglia are located in the adventitia [ 29 ]. In the mouse, catecholamine fibers were concentrated in the PV rather than in the LA appendage [ 30 ]. In the rat, the density of catecholamine fibers in the PV increased with post-natal age [ 31 ].…”
Section: Pulmonary Veins: An Anatomical Substrate Favorable To the Initiation And Conduction Of Ectopic Electrical Activitiesmentioning
confidence: 99%
See 1 more Smart Citation